2017
DOI: 10.3390/en10020184
|View full text |Cite
|
Sign up to set email alerts
|

Investigating How an Artificial Neural Network Model Can Be Used to Detect Added Mass on a Non-Rotating Beam Using Its Natural Frequencies: A Possible Application for Wind Turbine Blade Ice Detection

Abstract: Structures vibrate with their natural frequencies when disturbed from their equilibrium position. These frequencies reduce when an additional mass accumulates on their structures, like ice accumulation on wind turbines installed in cold climate sites. The added mass has two features: the location and quantity of mass. Natural frequencies of the structure reduce differently depending on these two features of the added mass. In this work, a technique based on an artificial neural network (ANN) model is proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Gantasala et al (2017) found n n e u = 8 and n s a m p l e = 343 as suitable parameters for a similar problem, where a nonlinear function is approximated for the data set consisting three inputs (first three natural frequencies of a cantilever beam) and three outputs (added masses at three different locations on the beam). Same values are used for n n e u and n s a m p l e in this study, and a data set consisting 343 samples is created for training the neural network model.…”
Section: Ann Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Gantasala et al (2017) found n n e u = 8 and n s a m p l e = 343 as suitable parameters for a similar problem, where a nonlinear function is approximated for the data set consisting three inputs (first three natural frequencies of a cantilever beam) and three outputs (added masses at three different locations on the beam). Same values are used for n n e u and n s a m p l e in this study, and a data set consisting 343 samples is created for training the neural network model.…”
Section: Ann Modelmentioning
confidence: 99%
“…Damage identification methods rely on the inverse problems (as shown in Figure 1(b)) where the location and severity of a damage in the structure are determined based on its modal properties. The authors of this article used an artificial neural network (ANN) model in Gantasala et al (2017) to solve such inverse problem for identifying added masses on a cantilever beam for any given set of natural frequencies of the corresponding beam. Initially, a data set of natural frequencies of the beam is created using its FEM model where different quantities of added masses are considered at different locations on the beam.…”
Section: Introductionmentioning
confidence: 99%
“…In previous literature, the beam axis is considered collinear to the rotation center [10,11]. Since their potential engineering background may be helicopter rotor blades [12], aircraft engine [13], robotic manipulators, and turbine blades [14,15]. For the machine gun system, considering the rotating beam with an axis eccentricity is more appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…The introduced method is proposed for an on-line and non-intrusive damage detection technique for vibrating systems. However, interesting work was conducted to detect the added ice mass on wind turbine blades [4]. The change in the blade natural frequencies due to the added mass was considered for this purpose.…”
Section: Introductionmentioning
confidence: 99%